High-resolution noncontact AFM and Kelvin probe force microscopy investigations of self-assembled photovoltaic donor–acceptor dyads - Grévin, Benjamin; Schwartz, Pierre-Olivier; Biniek, Laure; Brinkmann, Martin; Leclerc, Nicolas; Zaborova, Elena; Méry, Stéphane (Beilstein Journal of Nanotechnology, 2016)
Self-assembled donor–acceptor dyads are used as model nanostructured heterojunctions for local investigations by noncontact atomic force microscopy (nc-AFM) and Kelvin probe force microscopy (KPFM). With the aim to probe the photo-induced charge carrier generation, thin films deposited on transparent indium tin oxide substrates are investigated in dark conditions and upon illumination. The topographic and contact potential difference (CPD) images taken under dark conditions are analysed in view of the results of complementary transmission electron microscopy (TEM) experiments. After in situ annealing, it is shown that the dyads with longer donor blocks essentially lead to standing acceptor–donor lamellae, where the acceptor and donor groups are π-stacked in an edge-on configuration. The existence of strong CPD and surface photo-voltage (SPV) contrasts shows that structural variations occur within the bulk of the edge-on stacks. SPV images with a very high lateral resolution are achieved, which allows for the resolution of local photo-charging contrasts at the scale of single edge-on lamella. This work paves the way for local investigations of the optoelectronic properties of donor–acceptor supramolecular architectures down to the elementary building block level.
Keywords: donor–acceptor co-oligomers; donor–acceptor lamellae; donor–acceptor-ordered bulk heterojunction; Kelvin probe force microscopy (KPFM); noncontact atomic force microscopy (nc-AFM); organic photovoltaics; surface photo-voltage (SPV)